The importance of IT startups in sustainable agriculture - Mátyás, Bence (Tierra Infinita, 2019)
Number of studies investigating new technological tools is increasing because of their effect on the sustainable agriculture and environmental quality. Thanks to the introduced startup mentor- and incubator programs in Ecuador, many innovative solutions appeared recently on the global and on the international market. These startups contribute to improving agricultural productivity while minimizing negative impact on the environment. The objective of this study is to present some IT startups mentored by Coworking StartUPS program and discuss their importance in sustainable agriculture. Two main factors are highlighted in the study that these IT startups affect: Soil fertility and Crop yield. Most of these innovative solutions target the prevention of plant diseases by monitoring the pots and increase soil fertility by developing decision support tools.